Checklist and typification of Heterostemma (Apocynaceae, Asclepiadoideae, Ceropegieae) - Rodda, Michele (Phytotaxa, 2016)
All names in Heterostemma and their known synonyms are listed. Lectotypes are designated for 33 names and a neotype is designated for Stapelia quadrangula. Dittoceras is synonymised with Heterostemma and three new combinations are validated.